Do consumers recognise and associate purpose with real brands? Possible differences between leadership and sectors - Ventura, Adriana da Conceição (2022)
The impact that brands intend to make in the world and in society is increasingly valued by consumers, so organisations are becoming more concerned with their purpose and the way they communicate it. However, is the purpose of brands clearly recognised by consumers? This research aims to find the answer to this question and, furthermore, to understand the differences of recognition taking into consideration the leading position of brands in the market, as well as in different markets. With the main objective of analysing these topics, quantitative research was developed, through three different surveys that were shared online. Among the main findings is the fact that leading brands do not have higher levels of recognition of purpose compared to other brands. In addition, this study also revealed the consumer's affective and cognitive differences regarding the importance attributed to the purpose and its recognition. This research allowed to obtain results that provide interesting and relevant guidelines for brand marketing managers, professionals, and researchers, regarding the recognition of purpose by the consumer, in different sectors and with different levels of market positioning.